Environmental & architectural phenomenology. Vol. 2, issue 3 - (:unkn) unknown (Kansas State University. Architecture Department, 1991)
Vol. 2, No. 3, Fall 1991 (includes "citations received,” book review of Max Jacobson, Murray Silverstein & Barbara Winslow's The Good House, and essay by Yuan Lin).
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals